Kolaborasi Pentahelix dalam Pengembangan Akomodasi dan Pemasaran Wisata Budaya yang Ramah Lingkungan dan Berkelanjutan di Desa Wisata Taro - Ni Desak Made Santi Diwyarthi; Nyoman Gede Mas Wiartha; Fakhri Fakhrur Rozy; Ardhana Reswari Masykuri; I Wayan Jata (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the roles and challenges of accommodation management in supporting the sustainability of Taro Tourism Village, by examining the integration of cultural, local economic, and environmentally friendly aspects. The research adopts a qualitative approach with a case study method, focusing on field observations, in-depth interviews with homestay managers, village leaders, tourists, and regional policymakers, as well as a literature review based on the pentahelix theory. Data analysis was conducted through source and method triangulation to obtain a comprehensive understanding of the dynamics of accommodation management in the tourism village. The findings reveal that most accommodations in Taro Tourism Village are still managed conventionally, with a low level of adoption of environmentally friendly practices and digitalization. The local community plays a dominant role in operational aspects but remains less involved in strategic decision-making and digital marketing. This gap has caused accommodations to function suboptimally as instruments of local economic empowerment. Nevertheless, there is great potential for developing community-based homestays through multi-stakeholder (pentahelix) collaboration, integration with digital marketing, and capacity-building in sustainable service and management. Conceptually, this study emphasizes the importance of repositioning accommodation as a strategic element of cultural tourism. Practically, the results offer policy recommendations to strengthen the competitiveness of tourism villages in Bali through the development of accommodations oriented toward sustainability, community participation, and digital technology.